Modeling the Poverty Rate of East Java Using Quartile Smoothing Splines Regression - Dzakiir, Ammaar; Herlina, Marizsa (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Many research have shown that the Economically Active Participation Rate (EAPR) is influencing the poverty rate significantly in Indonesia. However, the complex relationship between EAPR and Poverty makes it impossible to use a simple regression analysis, because it has a non-parametric relationship. So, this study uses Quantile Smoothing Splines Regression to estimate curves at various quantiles. The purpose of this study is to estimate the model of the poverty rate based on EAPR East Java in 2023. The results show that at quantiles 0.25 with and 0.5 with , an increase in EAPR will increase poverty rate. However, at high EAPR, the effect is negative and very small. For quantiles 0.75 and 0.95 with , the effect of EAPR varies, showing positive and negative relationships that depend on the value of EAPR, with different and values at each range of EAPR values.